Branch number matters: Promoting catalytic reduction of 4-nitrophenol over gold nanostars by raising the number of branches and coating with mesoporous SiO2 - Ndokoye, P.; Zhao, Q.; Li, Xin Yong; Li, T.; Tade, Moses; Wang, Shaobin (Academic Press, 2016)
© 2016 Elsevier Inc. In this study, we demonstrate for the first time that highly branched gold nanostars (AuNSs) and silica-coated AuNSs (AuNSs@mSiO2) could potentially serve as efficient hydrogenation catalysts. The catalytic activity could be promoted by raising the number of tipped-branches of AuNSs, which reveals that the tips play an important role as active sites. The fabricated sharply-pointed AuNSs benefit the electron transfer from BH4 anions to 4-nitrophenol. Coating AuNSs with mesoporous silica (AuNSs@mSiO2) further enhanced the reduction rate and recyclability, and also contributed to reducing the induction period. The AuNSs@mSiO2 (50-100 nm in diameter) are large enough to be catalytically inactive, but they consist of sharply-pointed tips with the radius of 2.6-3.6 nm, which are rich in coordinately unsaturated sites similar to those of nanoparticles and clusters. Such features in structure and activity would also extend their application range in heterogeneous catalysis.